Pendampingan Two Stay Two Stray Pengelolaan Makanan Sehat Untuk Penguatan Literasi Keuangan dan Mencegah Fomo Kuliner Generasi Z SAS English Laboratory - Rizqy Fadhlina Putri; Nur Asyah; Rini Fadhillah Putri (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service is carried out through mentoring activities for SAS English Laboratory tutors, 89% of whom are Generation Z. The current habits and the ease of social media have poisoned the mindset of Generation Z to experience "FOMO" by following current trends, especially frequent culinary tours in cafes. Restaurants or street food, which lead to poor financial management, have become a problem for SAS English Laboratory tutors in managing their finances. 65% of the tutors agree that culinary news shared on TikTok has become a destination that must be visited, even if only for a photo. This activity was carried out with the two-stay two-stray method, dividing each group to manage easy-to-make and delicious food, followed by the application of science and technology in managing finances well. The results from this community service activity have opened the partners' minds to better financial management, contributing to more effective organization and use of finances. This, in turn, helps avoid consumerism in daily life, particularly in food consumption outside of home, such as in cafes or snack places. The partners stated that savings significantly differentiate the characteristics of the two clusters, or in other words, the indicators by respondents in the two existing clusters are very different from one aThis also helps the psychology of Generation Z in managing finances.